2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944531
|View full text |Cite
|
Sign up to set email alerts
|

Tactile afferents encode grip safety before slip for different frictions

Abstract: Adjustments to frictional forces are crucial to maintain a safe grip during precision object handling in both humans and robotic manipulators. The aim of this work was to investigate whether a population of human tactile afferents can provide information about the current tangential/normal force ratio expressed as the percentage of the critical load capacity - the tangential/normal force ratio at which the object would slip. A smooth stimulation surface was tested on the fingertip under three frictional condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Contact with slippery objects excites FA1 afferents more strongly than contact with a less slippery surface (Johansson and Flanagan 2009;Khamis et al 2014b). Accordingly, it has been proposed that FA1 mechanoreceptors could be exquisitely sensitive to mechanical deformations induced by microslips occurring at the papillary surface of the fingers (Delhaye et al 2012; Johansson and Flanagan 2009; Khamis et al 2014a). In this respect, the recent "slip hypothesis" proposes that cutaneous sensory coding of microslips could be indeed responsible for the force adjustments observed during lifting of slippery objects (Schwarz 2016).…”
Section: Sensorimotor Implications Of Skin Wetness Perception For Prementioning
confidence: 99%
“…Contact with slippery objects excites FA1 afferents more strongly than contact with a less slippery surface (Johansson and Flanagan 2009;Khamis et al 2014b). Accordingly, it has been proposed that FA1 mechanoreceptors could be exquisitely sensitive to mechanical deformations induced by microslips occurring at the papillary surface of the fingers (Delhaye et al 2012; Johansson and Flanagan 2009; Khamis et al 2014a). In this respect, the recent "slip hypothesis" proposes that cutaneous sensory coding of microslips could be indeed responsible for the force adjustments observed during lifting of slippery objects (Schwarz 2016).…”
Section: Sensorimotor Implications Of Skin Wetness Perception For Prementioning
confidence: 99%
“…Despite its crucial importance, the mechanical de-formation that underpins the encoding of the frictional strength on initial contact remains unclear. It is well known that the timing of the impulses of tactile afferents encodes the information related to force direction (10), local curvature (11), edges (12), shapes (13) and also contains information about the frictional strength (14, 15). One hypothesis suggests that, at the mechanical level, micro-slip events at the finger-object interface induce vibrations of the skin (16, 17).…”
mentioning
confidence: 99%
“…A previous study showed that information about grip safety, i.e. the increment of tangential force needed to reach full slip, is present in the response of local tactile afferents at the level of a population of afferents, irrespectively of the level of friction (Khamis et al, 2014). Given that all afferents respond to progressing slips, and that the timing of each FA-I afferent's burst is dependent on how far from the center of contact the afferent is, it is not surprising that a linear combination of multiple FA-I units can provide a good estimate of the grip safety.…”
Section: Discussionmentioning
confidence: 99%